V Міжрегіональні новорічні біологічні читання (Миколаїв, Україна, 9-10.12. 2005 р.) - Бойко, М.Ф. (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
V Міжрегіональні новорічні біологічні читання (Миколаїв, Україна, 9-10.12. 2005 р.)